Kronika polska, litewska, żmudzka i wszystkiéj Rusi (1582) Macieja Stryjkowskiego w perspektywie językoznawczej – stan i perspektywy badań (na przykładzie nazw żeńskich) - Zarębski, Rafał (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
This article discusses the state of research on the 16th-century chronicle Kronika polska, litewska, żmudzka i wszystkiéj Rusi (Chronicle of Poland, Lithuania, Samogitia and all of Ruthenia) by Maciej Stryjkowski, first published in 1582. Linguistic research to date (earlier studies by Zenon Klemensiewicz, Maria Karpluk, Karol and Zofia Zierhoffer and more recent studies – Olga Gaiseniuk’s doctoral thesis) has focused primarily on the phonetic, grammatical, lexical and onymic layer of the text, and to a lesser extent on the problem of the influence of other languages (Latin and Ruthenian languages) on the Polish language of the text. Using feminine names as an example, it is shown that the lexical material of the text can contribute to research in cultural linguistics. The role of women in ancient societies, although important and recognised by modern researchers, is not always sufficiently visible. This may be due to the range of themes and topics taken up in a given text, as is the case with Stryjkowski’s chronicle dominated by war issues, traditionally reserved mainly for men. In conclusion, the most important linguistic research perspectives on the text in question are indicated: pragmatic and discursive conditions as well as cross-cultural contexts related to social and moral transformations.